2017
DOI: 10.3727/152599517x14878772869603
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Charity Sport Events to Develop a Connection to a Cause

Abstract: Charity sport events can be strategically leveraged to provide benefits beyond the event itself. This study explores how charity sport events can be leveraged as an opportunity for nonprofit organizations to stimulate participants' interest in their other cause-related activities. Specifically, the relationships between motives for participation and future intentions to engage in additional cause-related activities are examined. Questionnaires were used to collect data at three separate and uniquely themed ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
(76 reference statements)
2
10
0
Order By: Relevance
“…For many NPOs, CSEs have become one of the most popular and effective fundraising tools (Goodwin et al , 2017). For example, Relay For Life (RFL), which is regarded as the largest CSE for the American Cancer Society, has raised nearly $6.5 billion to support for cancer research and prevention since its inception in 1985 (American Cancer Society, 2019).…”
mentioning
confidence: 99%
“…For many NPOs, CSEs have become one of the most popular and effective fundraising tools (Goodwin et al , 2017). For example, Relay For Life (RFL), which is regarded as the largest CSE for the American Cancer Society, has raised nearly $6.5 billion to support for cancer research and prevention since its inception in 1985 (American Cancer Society, 2019).…”
mentioning
confidence: 99%
“…However, an opportunity exists for exploration of how charity sport event managers can foster and activate this sense of community. Suggestions have been made for charity sport event managers to leverage social connectedness among participants to achieve important event objectives (Goodwin, Snelgrove, Wood, & Taks, 2017). Notably, Chalip, Green, Taks, and Misener (2016) revealed that there is an unfair expectation on event managers to foster social impacts from sport events, such as creating a sense of community.…”
Section: Charity Sport Eventsmentioning
confidence: 99%
“…Similarly, the theme of charitable contribution revealed that event managers positioned their event as a mechanism to support a specific charity while also giving back to the local community more broadly and educating community members on the needs of others. Stimulating interest in charitable activity has been highlighted as an important outcome of charity sport events (Goodwin et al, 2017).…”
Section: Charitable Contribution Shares Similarities With Administratmentioning
confidence: 99%
“…In addition, the genre of event being studied is expanding beyond the usual competitive sport event to also include charitable events (Goodwin, Snelgrove, Wood, & Taks, 2017;Snelgrove & Wood, 2010).…”
Section: Leveraging Eventsmentioning
confidence: 99%
“…While the majority of research on event leverage has focused on large-scale events, recent research has begun examining leveraging of small-scale events Goodwin et al, 2017;Pereira et al, 2015;Taks, Chalip, & Green, 2015;Taks et al, 2013). It has been suggested that small-scale events are more sustainable than large-scale events as they rely on the existing infrastructure, thereby reducing negative impacts such as debt, congestion and crowding (Gibson, Kaplanidou, & Kang, 2012;.…”
Section: Small-scale Eventsmentioning
confidence: 99%